Impact of plant-derived antioxidants on heart aging: a mechanistic outlook - Khoso, Muneer Ahmed; Liu, Heng; Zhao, Tong; Zhao, Wenjie; Huang, Qiang; Sun, Zeqi; Dinislam, Khuzin; Chen, Chen; Kong, Lingyi; Zhang, Yong; Liu, Xin (Frontiers in Pharmacology, 2025)
Heart aging involves a complex interplay of genetic and environmental influences, leading to a gradual deterioration of cardiovascular integrity and function. Age-related physiological changes, including ventricular hypertrophy, diastolic dysfunction, myocardial fibrosis, increased arterial stiffness, and endothelial dysfunction, are influenced by key mechanisms like autophagy, inflammation, and oxidative stress. This review aims to explore the therapeutic potential of plant-derived bioactive antioxidants in mitigating heart aging. These compounds, often rich in polyphenols, flavonoids, and other phytochemicals, exhibit notable antioxidant, anti-inflammatory, and cardioprotective properties. These substances have intricate cardioprotective properties, including the ability to scavenge ROS, enhance endogenous antioxidant defenses, regulate signaling pathways, and impede fibrosis and inflammation-promoting processes. By focusing on key molecular mechanisms linked to cardiac aging, antioxidants produced from plants provide significant promise to reduce age-related cardiovascular decline and improve general heart health. Through a comprehensive analysis of preclinical and clinical studies, this work highlights the mechanisms associated with heart aging and the promising effects of plant-derived antioxidants. The findings may helpful for researchers in identifying specific molecules with therapeutic and preventive potential for aging heart.